Evaluation of the Relationship Between Expression of Villin and Gelsolin Genes and Axillary Lymph Node Metastasis in Patients with Breast Cancer - Armin Borhan; Zohreh Nozarian; Alireza Abdollahi; Reza Shahsiah; Hadiseh Mohammadpour; Arash Borhan (Iranian Society of Pathology, 2021)
Background & Objective: Nowadays, actin-binding proteins such as Villin and Gelsolin have been considered to be associated with aggressive tumors. This study mainly aims to determine the relationship between Gelsolin and Villin genes expression and metastasis of axillary lymph nodes in patients with breast cancer.Methods: The included population consisted of 40 confirmed cases of female breast cancer (including 20 patients with breast cancer along with axillary lymph node metastasis and 20 patients without axillary lymph node metastasis). Expression of Villin and Gelsolin genes was evaluated using Real-time PCR and pre-designed primers.Results: The mean expression level of Villin in groups with and without axillary lymph node metastasis was 3.33±1.35 and 0.87±0.88, respectively (p <0.001). The mean Gelsolin expression levels in both groups (with and without axillary lymph node metastasis) were 4.13±2.40 and 1.00±0.35, respectively (p <0.001). The significant relationships were independent of individuals' age.Conclusion:  Patients with axillary lymph node metastasis may express significant higher level of Villin and Gelsolin gens.